Mothers' group participation: Associations with social capital, social support and mental well-being - Strange, C.; Bremner, A.; Fisher, C.; Howat, Peter; Wood, L. (2015)
© 2015 John Wiley & Sons Ltd. Aim: To investigate the relationships between participation in mothers' groups and social capital, social support and mental well-being measures for mothers whose oldest child was 0-5 years. Background: Evaluations of facilitated mothers' groups have found positive benefits for information sharing and support. Mothers' groups often continue as parent-led groups; however, little is known about the potential benefits of ongoing participation compared with non-participation. Design: Cross-sectional survey. Methods: Data were collected through a survey from March 2013-January 2014 in Perth, Western Australia. The data from a subgroup of mothers (N = 313) whose oldest child was 0-5 years of age were analysed using multivariable regression. Participation in mothers' groups in the previous 12 months was investigated for associations with social capital {Neighbourhood Cohesion Index (NCI); Families, Social Capital and Citizenship Survey (FSCCS) and Reciprocity}; social support {Medical Outcomes Study-Social Support Survey (MOS-SSS) and Parent Support Outside Home Scale (PSOHS)}; and mental well-being {Warwick Edinburgh Mental Well-Being Scale (WEMWBS)}. Participation was measured as three groups - locally, outside area of residence and non-participation. Results: Mothers who participated in mothers' groups locally scored significantly higher than those who had not participated in mothers' group for 'social capital' (NCI, FSCCS, Reciprocity), 'social support' (MOS-SSS, PSOHS) and 'mental well-being' (WEMWBS). Mothers who participated in mothers' group outside the area scored significantly higher than those who had not participated in mothers' groups for one measure of 'social support' (PSOHS). Conclusions: Participation in mothers' group locally may provide support and social capital benefits for mothers of children aged 0-5 years, which may influence mental well-being.